Empirical Scaling Laws of Neutral Beam Injection Power in HL-2A Tokamak - 曹建勇 魏会领 刘鹤 杨宪福 邹桂清 于利明 李青 罗翠文 潘宇东 姜韶风 雷光玖 李波 饶军 段旭如 (Chinese physics letters, 2015)
We present an experimental method to obtain neutral beam injection （NBI） power scaling laws with operating parameters of the NBI system on HL-2A, including the beam divergence angle, the beam power transmission efficiency, the neutralization efficiency and so on. With the empirical scaling laws, the estimating power can be obtained in every shot of experiment on time, therefore the important parameters such as the energy confinement time can be obtained precisely. The simulation results by the tokamak simulation code （TSC） show that the evolution of the plasma parameters is in good agreement with the experimental results by using the NBI power from the empirical scaling law.